ANALISIS PERMASALAHAN GURU TERKAIT PERANGKAT PEMBELAJARAN BERBASIS MODEL INQUIRY DAN PERMASALAHAN SISWA TERKAIT KEMAMPUAN PEMECAHAN MASALAH DALAM PEMBELAJARAN BIOLOGI DI SMA - Nuraini Nuraini; Makrina Tindangen; Elsje Theodora Maasawet (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2016)
The aim of this study is to obtain (1) description of the understanding level of high school teachers related biology learning tools through the Inquiry based learning model, (2) the solutions formulation to solve the problems of teachers solutions related to the development of Biology learning tools in high school, (3) description of the level of problem-solving skills of students related to learning biology-based Inquiry models, (4) the solutions formulation to solve the students problem solving skills related to Inquiry based biology learning model. The observation results of teachers and students problems were analyzed by descriptive qualitative showed that (1) the understanding level of teachers related inquiry based model of biology learning tools is still lacking, so its usage in the learning process has not done optimally, (2) Teachers have trouble in making learning tools. Therefore, teachers need a reference benchmark, mentoring activities and socialization in inquiry based learning model development, (3) Students are still difficult to solve problems in the learning process in the classroom, (4) lack of problem-solving skills students need to be addressed with the full guidance teacher to student related problem solving skills.Tujuan penelitian ini adalah untuk memperoleh (1) gambaran pemahaman guru SMA terkait perangkat pembelajaran Biologi melalui model pembelajaran berbasis Inquiry, (2) rumusan solusi dalam mengatasi permasalahan guru terkait pengembangan perangkat pembelajarann Biologi di SMA, (3) gambaran tingkat kemampuan pemecahan masalah siswa terkait pembelajaran Biologi berbasis model Inquiry, dan (4) rumusan solusi dalam mengatasi kemampuan pemecahan masalah siswa terkait pembelajaran Biologi berbasis model Inquiry. Hasil observasi permasalahan guru dan siswa yang dianalisis secara deskriptif kualitatif menunjukkan bahwa (1) pemahaman guru terkait perangkat pembelajaran Biologi berbasis model inkuiri masih kurang sehingga penggunaannya pada proses pembelajaran belum dilakukan secara optimal, (2) guru mengalami kendala dalam pembuatan perangkat pembelajaran. Oleh karena itu, guru memerlukan referensi acuan, kegiatan pendampingan dan sosialisasi dalam pengembangangan perangkat pembelajaran berbasis model Inquiry, (3) Siswa masih sulit dalam memecahkan permasalahan pada proses pembelajaran di kelas, dan (4) rendahnya kemampuan pemecahan masalah siswa perlu diatasi dengan bimbingan penuh guru kepada siswa terkait kemampuan pemecahan masalah.